PENGARUH RETURN ON EQUITY (ROE), DEBT TO EQUITY RATIO (DER), DAN TOTAL ASSET TURNOVER (TATO) TERHADAP PRICE EARNING RATIO (PER) (Studi Pada Perusahaan Sub Sektor Makanan Dan Minuman Yang Terdaftar Pada Bursa Efek Indonesia (BEI) Periode 2011-2016) - Rizky Famiah; Siti Ragil Handayani (Fakultas Ilmu Administrasi Universitas Brawijaya, 2018)
This study aims to determine and analyze the effect of Return On Equity (ROE), Debt to Equity Ratio (DER), and Total Asset Turnover (TATO) partially and simultanly on Price Earning Ratio (PER). This type of research used is explanatory research with a quantitative approach. The variables studied include Return On Equity (ROE), Debt to Equity Ratio (DER), and Total Asset Turnover (TATO) and Price Earning Ratio (PER). The research population is food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX). The sampling technique used is purposive sampling with criteria (1) food and beverage sub-sector companies listed on the IDX; (2) companies that publish financial statements for 6 consecutive years and have been audited for the 2011-2016 period; (3) the company has positive profits during the 2011-2016 period. Analysis of the data used in the form of descriptive statistics, classical assumption test, and multiple linear regression analysis. Kеywords: Return On Equity (ROE), Debt to Equity Ratio (DER), Total Asset Turnover (TATO), Price Earning Ratio (PER) АBSTRАK Penelitian ini bertujuan untuk mengetahui dan menganalisis pengaruh Return On Equity (ROE), Debt to Equity Ratio (DER), dan Total Asset Turnover (TATO) secara parsial dan simultan terhadap Price Earning Ratio (PER). Jenis penelitian ini yang digunakan adalah explanatory research dengan pendekatan kuantitatif. Variabel yang diteliti meliputi Return On Equity (ROE), Debt to Equity Ratio (DER), dan Total Asset Turnover (TATO) serta Price Earning Ratio (PER). Populasi penelitian ini adalah perusahaan sub sektor makanan dan minuman yang terdaftar pada Bursa Efek Indonesia (BEI). Teknik pengambilan sampel digunakan yaitu purposive sampling dengan kriteria (1) perusahaan sub sektor makanan dan minuman yang terdaftar di BEI; (2) perusahaan yang mempublikasikan laporan keuangan selama 6 tahun berturut-turut dan telah diaudit periode 2011-2016; (3) perusahaan memiliki laba positif selama periode 2011-2016. Analisis data yang digunakan berupa statistik deskriptif, uji asumsi klasik, dan analisis regresi linier berganda. Kаtа Kunci: Return On Equity (ROE), Debt to Equity Ratio (DER), Total Asset Turnover (TATO), Price Earning Ratio (PER)